2019
DOI: 10.2474/trol.14.353
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behavior of Hydrophilic and Hydrophobic Surfaces in Atmosphere with Different Relative Humidity

Abstract: The significant influences of atmospheric humidity on tribological phenomena are widely recognized. Although the influencing mechanisms of the humidity have been studied for a long time, many of the previous explanations remain in the qualitative estimation of mechanisms particularly from chemical effects viewpoint. In order to elucidate how the adsorbed water on a surface influences tribological phenomena, the current authors conducted ball to ball scratch tests for austenitic stainless steel (JIS SUS304) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The friction coefficient for 55% RH decreases gradually from 0.81 to 0.69 for a sliding speed of 20 to 200 µm•s −1 , then drops significantly to 0.36 when the sliding speed reaches 2000 µm•s −1 . For 95% RH, A previous study using the same conditions and tribotester also reported a similar observation where low to medium RH shows a larger variety of data [23]. Thus, the friction coefficient will have a larger range of values for all conditions except for 2000 µm•s −1 at 95% RH.…”
Section: Friction Coefficientsupporting
confidence: 61%
See 2 more Smart Citations
“…The friction coefficient for 55% RH decreases gradually from 0.81 to 0.69 for a sliding speed of 20 to 200 µm•s −1 , then drops significantly to 0.36 when the sliding speed reaches 2000 µm•s −1 . For 95% RH, A previous study using the same conditions and tribotester also reported a similar observation where low to medium RH shows a larger variety of data [23]. Thus, the friction coefficient will have a larger range of values for all conditions except for 2000 µm•s −1 at 95% RH.…”
Section: Friction Coefficientsupporting
confidence: 61%
“…The hypothesis put forward to explain these results was that RH contributes to the Laplace pressure within the water meniscus formed by the adsorbed water layer, resulting in unusually high lateral forces during specimen detachment. To further validate the physical effect of the adsorbed water layer in these peculiar observations, the tribological behavior of hydrophobic and hydrophilic materials was compared under different RH conditions [23]. In this experiment, PTFE samples did not exhibit any abnormal lateral force readings, whereas austenitic stainless steel samples consistently reproduced the peculiar phenomenon across all RH levels.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Various studies on different types of gas sensors have shown an unwanted effect of humidity on the responses to gases of interest [7]- [9]. Changes in the amount of humidity on different materials have different effects, depending on whether they are hydrophilic or hydrophobic materials [10]. The effect of humidity on hydrophilic materials can be macroscopic as well as microscopic while in the hydrophobic materials this effect is only visible microscopically [11].…”
Section: Introductionmentioning
confidence: 99%
“…For ceramics (e.g., SiC and Si 3 N 4 ), the wear is suppressed in humidity, water, and ionic liquid due to the formation of tribo-layers induced by the tribochemical reactions between the sliding interfaces ( Khanna et al, 2017 ; Qin et al, 2018 ; Chen et al, 2019 ; Ge et al, 2019 ; De Fine et al, 2021 ). Moreover, the wear behaviors between the contact surfaces of the metals or alloys in humidity or with lubricants are suppressed when the oxide layers are arisen by the tribochemical reactions ( Cai et al, 2009 ; Barthel et al, 2012 ; Fukuda et al, 2019 ; He et al, 2021 ). Accordingly, the previous experiments have evidenced that tribochemical reactions should play critical roles in the micro-/nano-scale wear (or material removal) of friction systems.…”
Section: Introductionmentioning
confidence: 99%